SWOT Analysis for Determining Marketing Strategy: A Case Study on Coal Mining Related Service Firm - Nella Oktaviana Wahyudi; Maria Y.D. Hayu Agustini; Agatha Ferijani (Soegijapranata Catholic University, 2023)
The purpose of this study aims to identify marketing strategy alternatives for the studied company is able to compete in higher intense competition in which more companies have been entering the market. Interview to the managers of the company was conducted to gather data on the marketing strategy it has applied. SWOT analysis using IFE matrix for describing strength and weakness factors and EFE matrix for opportunity and threat factors. The results indicate that the company is in quadrant I of IE matrix meaning that internally the company has strengths and externally it has opportunities. Appropriate strategy is to grow and build. The company can penetrate the market by offering new services to the existing clients, develop the market by addressing not only big companies but also the smaller ones, and develop product by creating new supporting services to the clients.